The Effect of Bacteriosin from Lactobacillus Acidopillus on Growth of Salmonella Typhi - Pratiwi, Siska Telly; Paryati, Sayu Putu Yuni (International Journal of Psychosocial Rehabilitation, 2020)
Antibiotic resistance is a global problem, especially in dealing with infections. WHO reports Southeast Asia has the highest number of cases of antibiotic resistance in the world. The irrational use of antimicrobials and the development of antibiotic resistance open interest in using natural antimicrobial alternatives such as bacteriocin. High bacteriocin diversity can prevent the emergence of resistance. Bacteriocin is a bioactive extracellular peptide that is bactericidal or bacteriostatic against pathogenic bacteria. Lactic acid bacteria are the group of bacteria that produce the most bacteriocin. One species of lactic acid bacteria is Lactobacillus acidopillus. The aim of this study was to examine the effect of bacteriocin from L. acidopillus on the growth of Salmonella typhi. In this research, identification of L. acidopillus single colonies was tested by morphological and biochemical characteristics, extraction of bacteriocin from L. acidopillus suspensions, and testing the antibacterial activity of bacteriocin against S. typhi growth by agar diffusion method. The analysis was carried out by looking at the formation of the diameter of the halo in the space around the bacteriocin space. L. acidopillus used were a bacterium with bacillus form, positive in Gram staining, negative in catalase and oxidase test. Extraction of bacteriocin from L. acidopillus suspension using the method by Ogunbanwo et al. (2003). In Muller Hinton agar that S.typhi had grown, a well was made containing bacteriocin, but no halo was formed. It caused by L. acidopillus used does not have the bacteriocin gene, the bacteriocin extraction method is not optimal, or the amount of bacteriocin produced were small. Therefore, further testing is needed regarding the testing of bacteriocin-forming genes in L. acidopillus, looking for other extraction methods by taking into environmental conditions of the growth of bacteria and modification methods for testing bacteriocin activity by adding sensitive antibiotics to the target bacteria as a control.